Development Process and Characteristics Study of Tree Line Discharge in 10 kV Overhead Power Lines - XU Huikai; HUANG Xiaolong; YANG Chunlan; CHEN Tianxiang; YANG Nongchao; CHEN Long (工程科学与技术)
ObjectiveThis study focuses on the development process and mechanism of tree line discharge. It examines the development characteristics of 10 kV overhead line tree line discharge, investigates variations in temperature and water content across different stages of discharge, proposes the development mechanism of the charring channel, and introduces a feature extraction method based on these findings.MethodsBased on the characteristics of a 10 kV three-phase ungrounded distribution network system during single-phase ground faults, an experimental platform for 10 kV overhead line tree discharges was constructed. Voltage transformers and sampling resistors were employed to collect voltages and currents. A typical species of pine tree was selected as the main object of study, and the tree samples were inserted into moist soil to ensure effective grounding. The entire tree discharge process was monitored through a synchronized acquisition system, and changes in temperature and electrical signals were recorded. An analysis of the temperature and water content changes across various cortical tissues of the tree was conducted to examine the progression of the discharge process triggered by contact between the tree and the power line. Infrared thermography was employed to observe the complete development of the charring channel under the tree epidermis. The mechanism of charring channel development under the tree epidermis was proposed, and its accuracy was verified using microscope images. Based on the observed characteristics of the tree discharge process, feature extraction was performed using high-frequency signals that contained detailed information on high-frequency discharges. The effectiveness of this method was verified using experimental data.Results and DiscussionsBased on the overall change in leakage current during tree line discharge, the process was divided into four stages: the contact and warming stage, the water evaporation stage, the charring channel development stage, and the flame bridging and arc ignition stage. The moisture distribution within the tree affected the development of current channels. During the transition from the contact and warming stage to the water evaporation stage, the passage of electric current through the tree shifted from the sapwood to the vascular cambium due to a temperature increase that enabled water migration from the tree. The rise in temperature and the reduction in water content initially caused an increase in leakage current, followed by a decrease, during the first two stages, both of which simultaneously created favorable conditions for the development of charring channels. The localized drying, breakdown, and charring within the tree, resulting from the temperature rise and moisture loss in the early stages, repeatedly occurred to form a forward-progressing charring channel. Microscopic observation of the discharge process at the front end of the charring channel confirmed this conclusion. The charring channel acted as a series resistor in the fault path, exhibiting low resistance, which led to a reduction in ground impedance as the channel developed. The correlation between the charring channel and the leakage current amplitude further validates the changes in tree impedance due to the formation of the charring channel. As the charring channel crosses the tree, the larger leakage current further ignites the tree, and the resulting surface flames cause a rapid drop in ground impedance, resulting in line-to-ground arcing along the tree. Based on these findings and analyses, a fault signal feature extraction method was proposed using high-frequency signal transient intensity statistics. Regions of higher energy concentration were identified by analyzing the statistical distribution of transient intensity, enabling effective differentiation between tree line discharge signals and background noise. The results demonstrated that the transient intensity probability distribution curve progressively flattens as the fault develops, further indicating that the development of tree line discharge is accompanied by changes in high-frequency discharge energy. The described tree line discharge development process and the proposed feature extraction method provide a foundation for forest fire traceability and the development of tree line discharge monitoring devices.ConclusionsThis study shows the high-frequency discharge details during the tree line discharge process. Existing tree line discharge models do not consider the high-frequency details, which can result in the neglect of significant features within the high-frequency signals of tree line discharges. These features can be manifested in electrical signals, as well as in ultrasonic and ground waves. The effectiveness of both ultrasonic and ground waves for high-frequency feature extraction was validated through experimental results. In addition, several issues emerged during the experimental process that differ from conventional single-phase grounding faults. For instance, the voltage amplitude of the faulted phase is not the lowest, and the zero-sequence voltage, which is typically expected to increase upon fault occurrence, instead exhibits a decrease in amplitude. The above phenomena can lead to misinterpretation by existing fault detection equipment. Therefore, investigating the underlying mechanisms of these phenomena is essential for a deeper understanding of tree line discharge faults.